The Use of Metaphor in Designing Ocean World Aquarium - Harisdani, D. D.; Deo Riza Sativa (Talenta Publisher, 2020)
Ocean World Aquarium design is a design for developing Cermin Beach Theme Park is located in Serdang Berdagai Regency, North Sumatera. This design depicts the sea and coastal life, such as the beach and the Mangrove forest. The application of metaphor in this architecture becomes one of the sell values of this building. The shape of coastal animals such as Crab is chosen as a metaphor for the building design. This Ocean Aquarium design is expected to benefit the community by becoming a recreational and educational place as well, and able to be a creative and educational vehicle in this Theme Park development tour